Implementasi Promosi Marketing Mix pada Usaha Toko Oki MKGR - Yandi Suprapto; Wiliana Halim (Indo Publishing, 2025)
The purpose of this article is to examine the implementation of the marketing mix promotion at the Oki MKGR Store. The identification results show a visible impact and improvement in Oki MKGR Store sales. This includes increased consumer brand awareness of the business, easier purchasing activities for buyers with WhatsApp, and increased daily sales from consumers viewing Oki MKGR Store content and posts on Instagram and Facebook.